2021
DOI: 10.1021/acs.jpcc.1c05623
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Mott Formula with Self-Assembled Monolayer (SAM)-Based Large-Area Junctions: Effect of Length, Backbone, Spacer, Substituent, and Electrode on the Thermopower of SAMs

Abstract: Understanding how the Seebeck effect of organic thermoelectric devices is associated with the chemical structure of active molecules within the devices is a key goal in organic and molecular thermoelectrics. This paper describes a series of physical–organic studies that investigate structure–thermopower relationships in self-assembled monolayers (SAMs) through measurements of the Seebeck coefficient (S, μV/K) using the eutectic gallium–indium (EGaIn)-based junction technique. Several hypotheses were derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 83 publications
3
45
0
Order By: Relevance
“…Molecular epitaxystepwise growth of (semi)­crystalline molecular overlayer on a substrateis useful for fabricating molecular thin films composed of vertically aligned, ordered oligomers from monomers. , Here, we show thermopower measurements over molecular junctions based on molecular epitaxy of an oligophenyleneimine (OPI n where n = 1–9) layer, formed via imine condensation between aryl aldehyde and amine derivatives on an ultrasmooth template-stripped gold (Au TS ) substrate (Figure ), , using eutectic Ga–In (EGaIn) for a top electrode (Figure ). , As the number of epitaxy cycles ( n in OPI n ) increased, the Seebeck coefficient ( S , μV/K) increased linearly. Notably, we observed a noticeable transition in the increasing rate at the point of n = 4 (length of molecule ( d ) = 3.4 nm), which was attributed to the transition in the charge transport regime from tunneling to hopping.…”
mentioning
confidence: 99%
“…Molecular epitaxystepwise growth of (semi)­crystalline molecular overlayer on a substrateis useful for fabricating molecular thin films composed of vertically aligned, ordered oligomers from monomers. , Here, we show thermopower measurements over molecular junctions based on molecular epitaxy of an oligophenyleneimine (OPI n where n = 1–9) layer, formed via imine condensation between aryl aldehyde and amine derivatives on an ultrasmooth template-stripped gold (Au TS ) substrate (Figure ), , using eutectic Ga–In (EGaIn) for a top electrode (Figure ). , As the number of epitaxy cycles ( n in OPI n ) increased, the Seebeck coefficient ( S , μV/K) increased linearly. Notably, we observed a noticeable transition in the increasing rate at the point of n = 4 (length of molecule ( d ) = 3.4 nm), which was attributed to the transition in the charge transport regime from tunneling to hopping.…”
mentioning
confidence: 99%
“…They are higher than those found for thiol-terminated alkyl chains, which were found to be 0.3 AE 1 and almost independent of length. 70 Studies [71][72][73][74] have also shown that increasing the applied temperature difference can lead to additional fluctuations in the thermovoltage. As a first step in the calculations leading to Table 1, energy barriers to rotation about the above axes were computed, to obtain the preferred angles of rotation, which minimise the total energy.…”
Section: Resultsmentioning
confidence: 99%
“…They are higher than those found for thiol-terminated alkyl chains, which were found to be 0.3 ± 1 and almost independent of length. 70 Studies 71–74 have also shown that increasing the applied temperature difference can lead to additional fluctuations in the thermovoltage.…”
Section: Resultsmentioning
confidence: 99%
“…toxicity, which enable their suitability not only for microfluidics, printed circuits, flexible electronics, and artificial intelligence, but also for biomedical applications. [10][11][12][13][14][15][16][17][18][19][20] Compared with "hard" NPs, "soft" NPs like Gallium and Gallium-Indium eutectic alloys (EGaIn, 75% Ga, 25% In, wt%) with moderate melting points (29.8 °C, 15.7 °C, respectively) possess good biocompatibility and low toxicity. More importantly, their mechanical parameters are close to biological tissue, which allows their in vivo administration, acrossing the biological barrier, and increased tissue retention.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, room temperature Gallium‐based liquid metal (LM) has attracted widespread interest due to its versatile physicochemical properties, [ 6–9 ] such as high electrical conductivity, flexibility, large surface tension, good biocompatibility, and low toxicity, which enable their suitability not only for microfluidics, printed circuits, flexible electronics, and artificial intelligence, but also for biomedical applications. [ 10–20 ] Compared with “hard” NPs, “soft” NPs like Gallium and Gallium‐Indium eutectic alloys (EGaIn, 75% Ga, 25% In, wt%) with moderate melting points (29.8 ℃, 15.7 ℃, respectively) possess good biocompatibility and low toxicity. More importantly, their mechanical parameters are close to biological tissue, which allows their in vivo administration, acrossing the biological barrier, and increased tissue retention.…”
Section: Introductionmentioning
confidence: 99%